A green protocol for peptide bond formation in WEB. Issue 21 (25th May 2016) - Konwar, Manashjyoti; Ali, Abdul Aziz; Sarma, Diganta
Graphical abstract: Highlights: Economical and environmentally friendly aqueous system as the medium. No external base is required for peptide coupling. Peptides are synthesized in water at room temperature. Organic solvents are not used. Abstract: A simple, efficient, and environmentally friendly approach has been developed for the synthesis of peptides in aqueous medium. In this work, peptides are easily synthesized in water extract of banana (WEB)/ethylene glycol and without using external base under mild condition.